Seasonal Variation of Lipid Profile of Oyster Crassostrea talienwhanensis from the Yellow Sea Area. Issue 4 (20th April 2020) - Liu, Yan-Fei; Wu, Zi-Xuan; Zhang, Jing; Liu, Yu-Xin; Liu, Zhong-Yuan; Xie, Hong-Kai; Rakariyatham, Kanyasiri; Zhou, Da-Yong
ABSTRACT: Lipid profile of the oyster Crassostrea talienwhanensis from the Yellow Sea was evaluated based on the seasonal changes in lipid categories, phospholipid (PL) categories, fatty acid (FA) composition, atherogenicity index (IA), thrombogenicity index (IT), and glycerophospholipid (GP) molecular species. We observed that the samples harvested in February contained higher levels of polyunsaturated fatty acid (PUFA) (48.77% of total FAs) and PL (52.12% of total lipids) and had lower IA (0.29). In addition, more than 290 GP molecular species of glycerophosphocholine (GPCho), glycerophosphoethanolamine (GPEtn), glycerophosphoserine (GPSer), and glycerophosphoinositol (GPIns) were determined. The molecular species containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) constituted 75.24% of total GPCho in the samples harvested in February. Considering the lipid profile, oyster Crassostrea talienwhanensis harvested in February had better nutritional value.